Finding Learning Strategy in Improving Science Literacy - Herlanti, Yanti; Mardiati, Yuke; Rahmawati, Rahmawati; Putri, Annisaa Meyrizka Kusumo; Jamil, Nurlaelah; Miftahuzzakiyah, Miftahuzzakiyah; Sofyan, Ahmad; Zulfiani, Zulfiani; Sugiarti, Sugiarti (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2019)
The result of science literacy in Indonesian students has been satisfactorily yet. The government has introduced some new learning strategies. The research is aimed to finding some learning strategies can improved literacy science. The research was conducted in Indonesian school involving 213 participants who are divided into study groups using several learning strategies. Research involved all student on 10 th grade in that school. Improvement of science literacy was analyzed by N-gain and comparing some strategies of learning was analyzed by Anova followed Turkey. The results shows the impovement of science literacy in the learning by using scientific approach was not as good as inquiry approach, Argument Driven Inquiry (ADI), and Science Technology Education Matematics (STEM). The results of science literacy finding the improvement in science literacy of students who learn by using scientific approach comparing using scientific approach is similar to the one using Science Technology Scociety (STS) strategy.